Intermittent Fasting and Its Health Implications: A Systematic Review of Existing Research - Jagoda Kubicka; Martyna Grabowska; Karolina Grabowska; Aleksandra Wiśniewska; Jakub Dąbek; Wiktoria Kosucka; Dominik Balik; Joanna Lara; Anna Kwasniewska; Karolina Kaszyńska (Quality in Sport)
Intermittent fasting (IF) strategy, including time-restricted eating (TRE), alternate day fasting (ADF), and other variations, is a dietary approach that alternates between periods of eating and fasting. This review investigates the influence of IF on human health, focusing on metabolic effects, cardiometabolic health, neurocognitive functions, and hormonal changes. IF is believed to help in weight reduction, improve insulin sensitivity, and reduce the risk of type II diabetes mellitus. It may also have positive impact on cardiovascular health by reducing blood pressure and improving lipid profiles. Moreover, IF is believed to have neuroprotective effects, improve cognitive functions and slow the progression of neurodegenerative diseases. Hormonal changes during IF are very complex and require careful management in conditions like hypothyroidism and Cushing's syndrome. Despite promising results, more research is needed to fully explore the potential negative outcomes and safety of IF. Choice of exact dietary protocol should be individualized and supervised by a healthcare provider.